Coalescence behavior of Cu nanoparticles during sintering: Based on atomic scale to macro scale - Jiaxin Liu; Weishan Lv; Yun Mou; Cai Chen; Yong Kang (Journal of Materials Research and Technology, 2023)
Due to the excellent electrothermal properties, outstanding resistance to electromigration and cost-effectiveness, Cu nanoparticles are considered as a promising bonding material for high-power device. However, few studies have analyzed the coalescence behavior mechanism of Cu nanoparticles during sintering under temperature dependent conditions. In this paper, a novel method combining atomic and macroscopic scales was adopted to investigate the coalescence behavior of Cu nanoparticles. The sintering microstructure and bonding quality of Cu nanoparticles at different temperatures were evaluated via in-situ Transmission electron microscopy (TEM) heating, and the evolution of dislocations and phase transitions was analyzed. Molecular dynamics (MD) simulation was employed to characterize the atomic scale evolution of solid-state liquid sintering process of Cu nanoparticles. The role of temperature and nanoparticle size in the sintering mechanism were investigated. The results indicate that high temperature during constant temperature sintering is beneficial for the formation of stable crystal structures in the sintering neck and reduces the generation of dislocations. Shockley dislocations can contribute to the constitution of HCP stacking fault within Cu nanoparticles, which deteriorates the sintering performance. The increase in sintering temperature prompts Cu atoms at the sintering neck to migrate horizontally rather than vertically. Compared to small-sized nanoparticles, significant driving energy was required in the sintering of large-sized nanoparticles during the continuous heating process. Shockley dislocations play a dominant role in phase transition stacking fault at high temperature. Additionally, the mechanical failure forms of Cu/Nano-Cu/Cu joints at different sintering temperatures were studied and verified through MD simulation.